Potential of unsubsidized distributed solar PV to replace coal-fired power plants, and profits classification in Chinese cities - Yang, Ying; Campana, Pietro Elia; Yan, Jinyue (Renewable & sustainable energy reviews, 2020)
This paper analyzes if solar photovoltaic technology is economically feasible enough to compete with coal-fired power in Chinese cities in the subsidy-free context. Considering this, this paper further investigates how profitable investing in solar PV projects is. This paper firstly analyzes to what degree local coal-fired power plants can be replaced by distributed solar power in 344 prefectural-level cities in China. Levelized Cost of Electricity of solar PV power and the local desulfurized coal benchmark price are used for simplified cost crossover math to identify the replacement risk of local coal-fired power plants. Four risk-levels and their corresponding cities are identified, i.e. deemed no cost-risk, potentially at cost-risk, at cost-risk, and substantially at cost-risk. As a whole, 85.17% of current coal-fired power plants from the investigated cities are under cost-risk. Levelized Profit of Electricity, Net Present Value, Internal Rate of Return, and Discounted Payback Period are calculated for each city, and grouped using K-means algorithm. The cities are clustered into four groups, i.e. high return, medium return, moderate return, and low return. The results show that 65.99% of all the cities could achieve a moderate or higher financial return. The cost-risk and investment profit results are mapped for a better understanding of the regional variation in China. •We use the cost crossover method to group 344 prefectural-level Chinese cities into four cost-risk levels.•We use the K-means clustering algorithm to group 344 prefectural-level Chinese cities into four investment-profit levels.•85.17% of current coal-fired power plants from the investigated cities are generally under cost-risk.•36.63% of them can be replaced by distributed solar PV projects.•Investing in 65.99% of the cities will achieve an IRR of higher than 8%, and a DPBP of less than 15 years.